Heart Diseases During Pregnancy - Trinidad, Dianolis; Cox, Rafael A. (Puerto Rico Health Sciences Journal, 2006)
Improvements in health care services in recent decades have permitted more frequent identification of pregnant women with congenital and acquired heart disease. Normal pregnancy and the peripartum period are associated with considerable cardiocirculatory changes, which are usually well tolerated by the mother. However, the increased cardiac demands imposed by those changes may at times unmask cardiac disease in presumably normal women or increase morbidity and mortality in women with established heart disease. A recognition and understanding of these changes is essential for providing optimal care to obstetrical patients with cardiac disorders. This article offers a brief review of those cardiocirculatory changes during pregnancy and of the main features of various congenital and valvular heart disorders frequently referred for advice to our cardiology practice, along with recommendations for their management and follow up.